Bimetallic nickel complexes for selective CO2 carbon capture and sequestration. Issue 3 (15th December 2015) - Möller, F.; Merz, K.; Herrmann, C.; Apfel, U.-P.
Abstract : Herein we report on the selective CO2 uptake from air by a dinickel azacryptand complex and its capability to act as a reversible CO2 storage system. Abstract : Herein we report a dinickel azacryptand complex that enables fast, selective, and tight CO2 binding from air. Exploiting the affinity of the cavitand towards azides, CO2 release was observed. Despite the stability of the azido complex, UV irradiation under atmospheric conditions proved to be a suitable pathway for N3 − replacement by CO2 .